Inkulturasi Liturgi sebagai Proses Transformasi: Studi atas Misa Inkulturasi di Paroki St. Klemens Mandonga, Kendari: Studi atas Misa Inkulturasi di Paroki St. Klemens Mandonga, Kendari - Huliandro Di’Almon Pan (Berkat : Jurnal Pendidikan Agama dan Katolik, 2026)
This study aims to analyze the role of liturgical inculturation in shaping the faith experience of the congregation through the practice of Inculturated Mass at St. Klemens Mandonga Parish. The study employed a descriptive qualitative approach combined with literature review and a survey involving 96 parish respondents. The findings indicate that most parishioners perceive inculturation as an encounter between Catholic faith and local culture that helps them experience their faith in a more contextual and meaningful way in everyday life. The practice of the Inculturated Mass is considered not only to enrich liturgical celebrations through the use of local cultural elements, but also to encourage active participation among the faithful during worship. In addition, liturgical inculturation fosters awareness of the importance of preserving local culture in harmony with Christian values. Such contextual liturgical experiences help deepen the spiritual relationship between the faithful and God, strengthen brotherhood within the community, and build a more inclusive and harmonious communal identity. Therefore, liturgical inculturation plays an important role in shaping a more vibrant, profound, and contextual experience of faith within both the Church and society.